ChemInform Abstract: Carbon—Hydrogen (C—H) Bond Activation at PdIV: A Frontier in C—H Functionalization Catalysis. Issue 12 (March 2015) - Topczewski, Joseph J.; Sanford, Melanie S.
Abstract Review: [20 refs.